Constructivism Analysis on the Influence of Practical Implementation on Computer Networks Course in Informatics Class - AHMAD DHAVI FAUZAN; PUTERI NOVARIQA; FRANSISCUS ATI HALIM (IJNMT (International Journal of New Media Technology), 2025)
Abstract - This research examines the effect of practicum sessions on improving learning outcomes in Computer Networking courses for Informatics students. The main issue explored is whether practical learning enhances theoretical understanding and technical skills better than traditional methods. A quantitative comparative approach was applied, analyzing secondary data of Midterm and Final Exam scores from two groups (one with practicum integration and one without). The results revealed significant performance differences, with the practicum group achieving higher scores, improved consistency, and lower variance compared to the non-practicum group. These findings highlight the positive impact of practical sessions on knowledge retention and skill development. The research concludes that practicum sessions play a critical role in effective learning for Computer Networking courses, suggesting the integration of hands-on activities in theoretical subjects. Further research could explore broader data sources to assess additional influencing factors.